2018
DOI: 10.1016/j.celrep.2018.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Periods for Cerebellar-Mediated Autistic-like Behaviors

Abstract: SUMMARYDespite a prevalence exceeding 1%, mechanisms underlying autism spectrum disorders (ASDs) are poorly understood, and targeted therapies and guiding parameters are urgently needed. We recently demonstrated that cerebellar dysfunction is sufficient to generate autistic-like behaviors in a mouse model of tuberous sclerosis complex (TSC). Here, using the mechanistic target of rapamycin (mTOR)-specific inhibitor rapamycin, we define distinct sensitive periods for treatment of autistic-like behaviors with sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 80 publications
5
82
0
Order By: Relevance
“…Its more robust outcomes may indicate a critical period for treating such a neurodevelopmental disorder. This is resonant of an elegant report on the sensitive periods for rescuing ASD-like behaviors in Tsc1-KO mice with an mTOR inhibitor rapamycin [68]. Future implementation of rescue paradigms with varying timing, dose and duration of DHA or chemogenetic administrations will help address the temporal constituent.…”
Section: Discussionmentioning
confidence: 89%
“…Its more robust outcomes may indicate a critical period for treating such a neurodevelopmental disorder. This is resonant of an elegant report on the sensitive periods for rescuing ASD-like behaviors in Tsc1-KO mice with an mTOR inhibitor rapamycin [68]. Future implementation of rescue paradigms with varying timing, dose and duration of DHA or chemogenetic administrations will help address the temporal constituent.…”
Section: Discussionmentioning
confidence: 89%
“…transmission occurs in SPNs of mice prenatally exposed to VPA. (Kwon et al, 2006;Ehninger et al, 2008;Zhou et al, 2009;Tsai et al, 2012Tsai et al, , 2018Gkogkas et al, 2013;Santini et al, 2013;Huynh et al, 2015) and VPA-treated rats (Cartocci et al, 2018), we asked whether prenatal exposure to VPA could result in altered repetitive and social behaviors.…”
Section: Prenatal Vpa Exposure Induces Impairments In Spns Synaptic Tmentioning
confidence: 99%
“…In fact, work from the Sahin's group showed that Tsc1-deletion or haploinsufficiency in Purkinje cells was sufficient to cause autistic-like phenotypes in mice (Tsai et al, 2012). Interestingly, these cerebellar-dependent social behaviour phenotypes could be rescued by continuous rapamycin treatment initiated either at P7 (Tsai et al, 2012) or at 6 postnatal weeks (Tsai et al, 2018) in homozygous, Purkinje cell-specific mutant mice. It is possible that the sensitive period to ameliorate the deficits of cell survival and excitability caused by Tsc1 deletion in Purkinje cells may be well into adolescence, later than that sufficient to rescue the deficits in cortical GABAergic PV interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities were only partially rescued by rapamycin treatment from P14-21. Thus, cerebellar impairments might contribute to the lack of rescue of social behavior deficits by early rapamycin treatment in the conditional homozygous mice (Tsai et al, 2018, Tsai et al, 2012.…”
Section: Short-term Administration Of Rapamycin Rescues Long-term Losmentioning
confidence: 99%